Impact of Conflict on Secondary School Education in Jos Jarawa Community of Jos North Local Government Area, Plateau State, Nigeria - Shittu Lukman Olayinka; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2025)
This study investigated the impact of conflict on secondary school education in Jos Jarawa community of Jos North Local Government Area of Plateau State, Nigeria. The study was guided by three objectives and three corresponding research questions were also answered in the study. The study adopted a mixed-method approach, integrating both qualitative and quantitative research designs. The research population included two public secondary schools, comprising 25 teachers and 315 students, from which 22 participants (2 teachers and 20 students) were purposively sampled for their direct experience with the conflict. The interviews provided in-depth qualitative insights, while the questionnaires captured structured quantitative data on educational resource availability and adequacy during and after the conflict. Experts validated the instruments to ensure content accuracy, and their reliability was tested using Cronbach's Alpha and KR-21 methods. Data collection was conducted in person, with questionnaire distribution and face-to-face interviews. The analysis of questionnaire data employed descriptive statistics through SPSS, while interview responses were transcribed and thematically analysed using NVivo software. The study revealed that, conflict significantly disrupts students’ academic performance by distorting the academic calendar, causing psychological trauma, and increasing school dropouts and also undermines the roles and productivity of teachers. It disrupts teaching schedules, increases their workload among others. The study recommended among other things that, teachers should be provided with continuous professional development opportunities, especially in conflict-sensitive education methods and Schools in conflict-affected areas should implement psychosocial support programmes for both students and teachers to help mitigate the trauma and psychological distress caused by conflict among others.